Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jid.2015.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Dysplastic Nevi from Common Melanocytic Nevi by Cellular and Molecular Criteria

Abstract: Dysplastic nevi (DNs), also known as Clark's nevi or atypical moles, are distinguished from common melanocytic nevi by variegation in pigmentation and clinical appearance, as well as differences in tissue patterning. However, cellular and molecular differences between DNs and common melanocytic nevi are not completely understood. Using cDNA microarray, quantitative RT-PCR, and immunohistochemistry, we molecularly characterized DNs and analyzed the difference between DNs and common melanocytic nevi. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…CMN contained 380 unique DEGs, with enrichment for biological processes revolving around extracellular matrix organization, including endodermal cell differentiation, collagen catabolism and cell adhesion (Figure B). Previous work demonstrated that DN can be molecularly distinguished from CMN, with DN being characterized by dysplasia of the epidermal‐melanin unit and aberrant expression of hair follicle‐related proteins . Thus, we focused our analysis on molecular differences and similarities between DN and MM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CMN contained 380 unique DEGs, with enrichment for biological processes revolving around extracellular matrix organization, including endodermal cell differentiation, collagen catabolism and cell adhesion (Figure B). Previous work demonstrated that DN can be molecularly distinguished from CMN, with DN being characterized by dysplasia of the epidermal‐melanin unit and aberrant expression of hair follicle‐related proteins . Thus, we focused our analysis on molecular differences and similarities between DN and MM.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue was never destroyed en bloc in the event that the pathologist thought diagnostic information was needed from the frozen sections. As described in our previous study, DN were classified by an experienced dermatopathologist using cytological and architectural features . Melanocytic nuclear atypia was noted if irregular, hyperchromatic or with prominent nucleoli.…”
Section: Methodsmentioning
confidence: 99%
“…Dsg1 regulates KC differentiation (Getsios et al, 2009;Harmon et al, 2013), (Jobe et al, 2016;Payne & Cornelius, 2002). In fact, CXCL1 was one of the most highly modified markers allowing discrimination between common melanocytic and dysplastic nevi (Eliades & Tsao, 2016;Mitsui et al, 2016). An altered inflammatory microenvironment contributes to the growth and invasion of transformed MCs and melanoma cells (Richmond, Yang, & Su, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Next, by screening the full characteristics and the quality control, 312 datasets were excluded. Therefore, only 3 datasets from GEO were selected, with samples from melanocytes [GSE38312 (17), n=5], nevi [GSE53223 (18), n=5], and melanoma stages I, II and III [GSE15605 (19), n=40]. Primary melanomas at stage IV and metastatic melanoma samples were excluded to simplify the analysis of gene expression changes that occur during the early transformation of non-cancerous cells (melanocytes or nevi) to melanoma cells.…”
Section: Resultsmentioning
confidence: 99%